Liturgical Opportunities for 'Deep Crying unto Deep': The Rhetorical Function of Now/Then Dualities in Gertrude of Helfta - Johnson, Ella (Medieval mystical theology, 2015)
While often praised for her generally strong female and positive self-imagery, Gertrude the Great of Helfta consistently lapses into body and self-pejorative language, especially in her Spiritual Exercises. This article investigates these consistent (albeit infrequent) pejorative images. Because they are found almost exclusively within the Exercises, and not throughout Gertrude's corpus, the article argues that they should be interpreted with a view to the special demands of the context in which they occur - that is, the genre of medieval monastic meditation. The article demonstrates that Gertrude uses the pejorative language in the context of a tension she builds between now/then or already and not yet, with the rhetorical function to set into greater relief moments of Eucharistic reconciliation and continuity between now/then that correlate with her affirmative images. The article concludes with two important implications for Gertrudian studies.